Effect of traditional Chinese medicine combined with conventional Western medicine for patients with severe/very severe chronic obstructive pulmonary disease: a multi-center, randomized, double-blind, controlled study - Jiansheng Li; Yang Xie; Minghang Wang; Suyun Li; Xuefeng Yu; Nianzhi Zhang; Zhengang Zhu; Wei Zhang; Jihong Feng; Zikai Sun; Lin Lin; Zhijia Sun; et al. (Chinese Medicine)
Abstract Background Traditional Chinese medicine (TCM) is widely used in the management of chronic obstructive pulmonary disease (COPD). This study aimed to evaluate the clinical efficacy of comprehensive therapy based on TCM patterns for patients with stable, severe to very severe COPD. Methods A multicenter, randomised, double-blind, placebo-controlled trial was conducted. Eligible patients were randomly allocated in equal proportions to two groups: the trial group, which received TCM-based therapy with Bu-Fei Jian-Pi, and Bu-Fei Yi-Shen, and Yi-Qi Zi-Shen granules tailored to TCM syndromes, and the control group, which received a placebo resembling Chinese medicine. Both groups also received conventional Western medicine as part of their treatment. Acute exacerbations (AEs), lung function, dyspnea scores, the 6-min walking test (6MWT), and the COPD assessment test (CAT) were assessed over 12 months of treatment, with an additional 12 months of follow-up. Results A total of 467 patients were included in the analysis with 228 in the experimental group and 239 in the control group. The Chinese herbal granules group significantly reduced AEs (0.63 vs. 1.03 events, P = 0.002), improved mMRC scores (−0.17 points, 95% CI −0.30 to −0.03; P = 0.015), 6MWT (29.24 m, 95% CI 10.71–47.77; P = 0.002), and CAT (−3.11 points, 95% CI −4.13 to −2.09, P < 0.001), compared with the control group. No significant differences were observed between the two groups in terms of FVC (l) and FEV1 (both in litres and as percentage). Conclusion Comprehensive therapy based on TCM patterns demonstrated efficacy in patients with severe to very severe COPD, reducing the frequency of AEs, improving dyspnea and exercise capacity, and alleviating symptoms. Trial registration: ClinicalTrials.gov, NCT02270424. Registered 17 October 2014, https://clinicaltrials.gov/study/NCT02270424?id=NCT02270424&rank=1 .